Terence and the verb 'to be' in Latin - Pezzini, Giuseppe (Oxford classical monographs, 2015)
This is an in-depth study of the verb 'to be' in Latin (esse) and its contracted form, with a particular focus on its appearance in the plays of the ancient Roman playwright, Terence